Hydrogen from methanol-steam reforming. Isothermal and adiabatic monolith reactors' simulation - Gonzo, Elio Emilio (2008)
In this work a simple, precise and fast procedure to simulate monolith reactors where the methanol-steam reforming reaction is carried out is presented. The technique accounts for the interfacial heat and mass transport limitations and the diffusion reaction process in monolith reactors with catalytic washcoat of nonuniform thickness. The monolithic reactor simulations were carried out considering a square channel of various sizes, different washcoat distributions (filled in square, circle in square) and taken into account isothermal or adiabatic operation. The global effectiveness factor profiles for the isothermal and adiabatic processes are shown. The bulk fluid temperature, the difference between bulk fluid and washcoat temperature profiles, and methanol conversion curves are also depicted. Comparison with experimental data of other authors as well as with results obtained using a robust, but time-consuming, numerical method for computing effectiveness factor showed a very good agreement.